2020
DOI: 10.1136/bmjopen-2019-036638
|View full text |Cite
|
Sign up to set email alerts
|

Productivity losses among people with back pain and among population-based references: a register-based study in Sweden

Abstract: ObjectiveBack pain is the leading cause for years lived with disability globally and among the main reasons for sickness absence (SA) and disability pension (DP). The objective of this study was to explore the occurrence of SA and DP and to estimate productivity losses among individuals with back pain compared with among matched population-based references.DesignExplorative prospective cohort study using register microdata.Participants and settingA total of 23 176 people, aged 19–60 years, with a first visit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Another specific interest of this study was to investigate the role of pain and/or CMD to the associations between psychosocial working conditions and three different SA measures. Based on the earlier research, we expected them to play a role 13–18 . Only pain seemed to affect the associations, but the effect varied for the different SA measures of this study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Another specific interest of this study was to investigate the role of pain and/or CMD to the associations between psychosocial working conditions and three different SA measures. Based on the earlier research, we expected them to play a role 13–18 . Only pain seemed to affect the associations, but the effect varied for the different SA measures of this study.…”
Section: Discussionmentioning
confidence: 81%
“…A recent meta-analysis indicated that psychosocial stressors at work (ie, job demands, job control, and social support) were associated with an increased risk of SA due to mental disorders 13 . Furthermore, pain and common mental disorders (CMDs), including anxiety, and depression, are known to be linked with increased risk of SA 14–18 . However, how pain and/or CMDs might influence the associations between psychosocial working conditions and SA is far less studied, especially in association with SA due to circulatory diagnoses.…”
mentioning
confidence: 99%
“…In our study, Higher SES scores were found to reduce the prevalence of mental disorders (including depression, anxiety, and stress) in both men and women. In a great study of approximately one million people living in 55 regions of Sweden, factors such as low social support, social humiliation, low employment status, and economic problems were found to be independently associated with mental health symptoms; however, education had no signi cant effect on the participants' mental health status (35). According to Wang et al, a low SES contributes to the development of major depressive disorder in the general Canadian population; however, this association depends on factors of gender and employment status.…”
Section: Discussionmentioning
confidence: 92%
“…Although LBP-associated sick leave is known to cause substantial indirect costs, estimates of these costs from recent studies vary widely, ranging from ~€3000 to ~€16 000 per episode [ 11 , 12 ]. A reason for this variation could be that it is unclear what underlying LBP diagnoses are associated with sick leave costs, as studies either do not differentiate between LBP diagnoses or only focus on one type of LBP [ 13 , 14 ]. Only one known study distinguished several LBP diagnoses [ 11 ].…”
Section: Introductionmentioning
confidence: 99%